Uma Ferramenta para Dar Suporte à Avaliação de Sistemas Colaborativos - Agostinho, Anderson M. C.; Varjolo, Luciana C.; Santos, Neide (Cadernos do IME - Série Informática, 2009)
Anderson M. C. Agostinho, Luciana C. Varjolo, Neide Santos